2020
DOI: 10.1101/2020.01.15.907568
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pathogens, endosymbionts, and blood-meal sources of host-seeking ticks in the fast-changing Maasai Mara wildlife ecosystem

Abstract: Background:The role of questing ticks in the epidemiology of tick-borne diseases in Kenya's Maasai Mara National Reserve (MMNR), an ecosystem with intensified human-wildlifelivestock interactions, remains poorly understood. Therefore, we carried out a survey of the diversity of questing ticks, their blood-meal hosts, and tick-borne pathogens to understand potential effects to human and livestock health.Methods: Questing ticks were collected by flagging and hand picks from vegetation in 25 localities and identi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…We recently found T. parva more frequently inRh. appendiculatus (15.7% of tick pools) sampled in the Maasai Mara National Reserve, where no Babesia was detected (Oundo et al, 2020). The absence of T. parva in animal blood samples in this study may be partly explained by its biology, where most of its life cycle is found in the lymphoid system and only multiplies in RBC for completion of its life cycle (Mans et al, 2015).…”
Section: Rickettsia Africae In Ticks and Licementioning
confidence: 62%
See 3 more Smart Citations
“…We recently found T. parva more frequently inRh. appendiculatus (15.7% of tick pools) sampled in the Maasai Mara National Reserve, where no Babesia was detected (Oundo et al, 2020). The absence of T. parva in animal blood samples in this study may be partly explained by its biology, where most of its life cycle is found in the lymphoid system and only multiplies in RBC for completion of its life cycle (Mans et al, 2015).…”
Section: Rickettsia Africae In Ticks and Licementioning
confidence: 62%
“…variegatum ticks collected mostly from cattle. Ever since the first description in Kenya of R. africae in Amblyomma ticks from the Maasai Mara region (Macaluso et al, 2003), high infection rates in Amblyommaticks have been reported at SHs in Mombasa and Nairobi (Mutai et al, 2013), Siaya County, which borders Busia County (Maina et al, 2014), pastoral communities in North Eastern Kenya (Koka et al, 2017), the Shimba Hills National Reserve (Mwamuye et al, 2017), Baringo County (Omondi et al, 2017), and the Maasai Mara National Reserve (Oundo et al, 2020). Rickettsia africae has similarly been reported inAmblyomma ticks from Cameroon , Zimbabwe (Beati et al, 1995), Senegal (Kelly et al, 2010), and the Central African Republic (CAR) (Dupont et al, 1995).…”
Section: Rickettsia Africae In Ticks and Licementioning
confidence: 99%
See 2 more Smart Citations
“…We were able to identify blood-meals from wild-caught non-engorged flies. Unlike serological and other PCR-based techniques for blood-meal identification [57,70,71], the use of HRM to detect sequence variants is fast, cost-effective, accurate, easy-to-use, and sensitive, making it a more economical tool for blood-meal analysis [30,72] and pathogen detection/identification [71,73,74]. Sequencing of representative samples with combined human-hippopotamus and human-African buffalo peaks confirmed their mixed blood-meal status (S2 Fig.…”
Section: Discussionmentioning
confidence: 99%